Gravettian weaponry: 23, 500-year-old evidence of a composite barbed point from Les Prés de Laure (France). (December 2018) - Tomasso, Antonin; Rots, Veerle; Purdue, Louise; Beyries, Sylvie; Buckley, Mike; Cheval, Carole; Cnuts, Dries; Coppe, Justin; Julien, Marie-Anne; Grenet, Michel; Lepers, Christian; M'hamdi, Mondher; et al.
Abstract: Understanding hunting technology is pivotal in the study of adaptive and innovative forces that influenced the evolution of prehistoric societies. The manufacture, design and use of hunting weapons involve technical processes such as those of tool miniaturization, blank standardization and projection modes, but also influence broader demographic structures such as human subsistence strategies, territorial organization and socio-economic structures. Here we present a unique discovery from a newly discovered site at Les Prés de Laure (Var, France). Excavations revealed a multi-stratified open-air site with archaeological units that were rapidly buried by the alluvium of the Jabron River. In a Gravettian layer dated between 25 and 23.5 ka cal BP, within an area apparently dedicated to horse carcasses processing and consumption, 11 backed points were discovered in direct association with altered bone remains. Wear and residue analysis of the lithic backed points in combination with complementary experimental data converge to indicate that the find represents a bone point armed with lithic barbs and used as hunting weapon. This discovery provides new evidence for the manufacture and use of hunting weaponry in a Gravettian context and stimulates discussion on Paleolithic weapon function and design, offering a unique window into the characterization of prehistoric hunting strategies. Highlights: A composite projectile point made of an osseous point and 11 lithic barbs was found at Les Prés de Laure in France. This discovery dating to 23.5 ka cal. BP significantly pushes back the oldest evidence for the use of barbed osseous points. A multidisciplinary study allows to propose a likely restitution of the design of the composite barbed point.